Pelatihan Literasi Media Digital dan Public Speaking bagi Komunitas Piwulang Becix Yogyakarta - Pupung Arifin; Immanuel Dwi Asmoro Tunggal (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2026)
Homeschooling in Indonesia is recognized as an alternative form of education that provides flexibility in the learning process. However, many people still lack a clear understanding of its benefits and challenges, particularly in developing children's practical skills. This community service program aims to develop public speaking and digital media literacy skills among children and adolescents through activities implemented by the Piwulang Becix Community in Yogyakarta. The method used is an interactive approach, including audiovisual media training, social media literacy, and public speaking techniques. Children are introduced to various audiovisual technologies, such as green screens and virtual reality, to stimulate their creativity and engagement in learning. The results of this activity indicate an improvement in children's skills in using digital media more critically and responsibly, as well as increased confidence in speaking in public. However, several challenges are still found, especially anxiety when speaking in front of an audience among some participants. Overall, this program provides a more personal, contextual, and applicable learning experience related to digital media and public speaking. It is expected that this training can serve as adequate initial preparation for children to face the challenges of digital media more wisely and effectively in the future.